2019
DOI: 10.1186/s13287-019-1300-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms utilized by feline adipose-derived mesenchymal stem cells to inhibit T lymphocyte proliferation

Abstract: Background: Feline adipose-derived mesenchymal stem cells (ASCs) have been successfully used in clinical trials for the treatment of immune-mediated diseases with T cell dysregulation. However, the immunomodulatory pathways utilized by feline ASCs to suppress T cell activation have not been fully determined. We investigated the mechanisms used by feline ASCs to inhibit T cell proliferation, including the soluble factors and the cell-cell contact ligands responsible for ASC-T cell interaction. Methods: The immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 61 publications
2
32
0
Order By: Relevance
“…Similar to what was described earlier for equine BM-derived MSCs, our results show that cyclooxygenase (COX) pharmacological inhibition restores the proliferation of lymphocytes in co-culture with MSCs (45,46). Since PGE 2 was identified as a molecule secreted in the culture media of human MSCs (61), it has been described as a major mediator of MSCs modulatory effects in several species (11,37,53,62), not only inhibiting lymphocyte proliferation, but also inhibiting the expression of co-stimulatory molecules by antigen presenting cells (APCs), thus limiting their capacity to activate T cells. Additionally, MSCs produce PGE 2 in sufficient quantity to be able to reprogram macrophages, thus inhibiting production of TNF-α and IL-6 and increasing the secretion of IL-10 (63, 64).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar to what was described earlier for equine BM-derived MSCs, our results show that cyclooxygenase (COX) pharmacological inhibition restores the proliferation of lymphocytes in co-culture with MSCs (45,46). Since PGE 2 was identified as a molecule secreted in the culture media of human MSCs (61), it has been described as a major mediator of MSCs modulatory effects in several species (11,37,53,62), not only inhibiting lymphocyte proliferation, but also inhibiting the expression of co-stimulatory molecules by antigen presenting cells (APCs), thus limiting their capacity to activate T cells. Additionally, MSCs produce PGE 2 in sufficient quantity to be able to reprogram macrophages, thus inhibiting production of TNF-α and IL-6 and increasing the secretion of IL-10 (63, 64).…”
Section: Discussionsupporting
confidence: 82%
“…Multiple soluble mediators have been described as relevant in the inhibitory effect of MSCs on lymphocyte proliferation (33). Although precise mechanisms seem to be speciesdependent, prostaglandin E 2 (PGE 2 ) secretion, indoleamine 2,3dioxygenase (IDO) activity and nitric oxide (NO) production seem to be the most common events across species (34)(35)(36)(37). Although there is sufficient evidence on the in vitro modulatory effect of MSCs on the immune response, there are disparate results between the beneficial effect of MSCs in preclinical models and their actual use in clinical diseases related to the immune system (38,39).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that blockade of ICAM-1 and VCAM-1 ablates MSC-mediated immunosuppression which highlights the potential mechanistic role of adhesion molecules by MSCs [ 60 ]. The role of ICAM-1/LFA ligand has been shown to play a critical role in feline ASC-mediated immunosuppression through induction of G0-G1 cell cycle arrest [ 61 ]. Feline ASCs also induce cell cycle arrest by utilizing PGE 2 which is comparable to our findings in dog MSCs, suggesting ICAM-1 may also play a significant role in canine MSC mediated immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports using feline stem cells in therapeutic studies in cats. The stem cells used in most cases have been shown to originate from feline adipose tissue [ 16 , 17 , 18 , 19 , 50 , 51 ]. With regard to potential therapeutic uses, there is a need for a source of stem cells of established diversity.…”
Section: Discussionmentioning
confidence: 99%